Herpes zoster in infants. - Dobrev, H. (European Journal of Pediatric Dermatology, 2018)
The Author has described four infants with Zoster under the age of one year who have had no history of chickenpox. However, a history of maternal varicella in the early life or during pregnancy is elicited in 2 cases. One of these infants have had intimate contact with his father who has developed varicella. Zoster in infancy develops after having asymptomatic fetal Varicella-Zoster Virus (VZV) infection or unrecognized episode of varicella in infants born to a VZV-immune mother.